Endothelial cells are not productively infected by SARS‐CoV‐2. Issue 10 (24th October 2021) - Schimmel, Lilian; Chew, Keng Yih; Stocks, Claudia J; Yordanov, Teodor E; Essebier, Patricia; Kulasinghe, Arutha; Monkman, James; dos Santos Miggiolaro, Anna Flavia Ribeiro; Cooper, Caroline; de Noronha, Lucia; Schroder, Kate; Lagendijk, Anne Karine; et al.
Abstract: Objectives: Thrombotic and microvascular complications are frequently seen in deceased COVID‐19 patients. However, whether this is caused by direct viral infection of the endothelium or inflammation‐induced endothelial activation remains highly contentious. Methods: Here, we use patient autopsy samples, primary human endothelial cells and an in vitro model of the pulmonary epithelial–endothelial cell barrier. Results: We show that primary human endothelial cells express very low levels of the SARS‐CoV‐2 receptor ACE2 and the protease TMPRSS2, which blocks their capacity for productive viral infection, and limits their capacity to produce infectious virus. Accordingly, endothelial cells can only be infected when they overexpress ACE2, or are exposed to very high concentrations of SARS‐CoV‐2. We also show that SARS‐CoV‐2 does not infect endothelial cells in 3D vessels under flow conditions. We further demonstrate that in a co‐culture model endothelial cells are not infected with SARS‐CoV‐2. Endothelial cells do however sense and respond to infection in the adjacent epithelial cells, increasing ICAM‐1 expression and releasing pro‐inflammatory cytokines. Conclusions: Taken together, these data suggest that in vivo, endothelial cells are unlikely to be infected with SARS‐CoV‐2 and that infection may only occur if the adjacent pulmonary epithelium is denuded (basolateral infection) or a high viral load is present in the blood (apical infection). In such a scenario, whilst SARS‐CoV‐2 infection of the endothelium can occur, it does not contribute to viral amplification. However, endothelial cells may still play a key role in SARS‐CoV‐2 pathogenesis by sensing adjacent infection and mounting a pro‐inflammatory response to SARS‐CoV‐2. Abstract : We show that endothelial cells are not productively infected with SARS‐CoV‐2 but mount a pro‐inflammatory response to the virus.